2021
DOI: 10.1111/ene.14960
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of primary lateral sclerosis and amyotrophic lateral sclerosis: Supplementary evidence for a continuum

Abstract: Background and purpose: Primary lateral sclerosis (PLS) is a motor neuron disorder characterized by a pure upper motor neuron degeneration in the bulbar and spinal regions.The key difference with amyotrophic lateral sclerosis (ALS) is the lower motor neuron system integrity. Despite important literature on this disease, the pathophysiology of PLS remains unknown, and the link with ALS still balances between a continuum and a separate entity from ALS.Methods: We report nine families in which both PLS and ALS ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Although we agree with the comments of these authors, we would like to mention several findings in favour of a continuum between PLS and ALS [1]. First, continuum does not mean progression from one side of the spectrum to the other in all cases but just different phenotypes of the same phenomenon.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Although we agree with the comments of these authors, we would like to mention several findings in favour of a continuum between PLS and ALS [1]. First, continuum does not mean progression from one side of the spectrum to the other in all cases but just different phenotypes of the same phenomenon.…”
supporting
confidence: 83%
“…First, continuum does not mean progression from one side of the spectrum to the other in all cases but just different phenotypes of the same phenomenon. Secondly, we stress the relevant literature supporting that PLS is associated with other motor neuron disorders, whether ALS, spinal muscular atrophy and frontotemporal lobar dementia, in the same family [1][2][3]. Moreover, many genes linked to ALS (C9orf72, FIG4, OPTN, UBQLN2) have also been found mutated in PLS patients [4].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Dear Editor, In their article, Corcia et al describe a series of nine patients suffering from primary lateral sclerosis (PLS) coming from different family clusters, in which every individual had a first-or second-degree relative affected by amyotrophic lateral sclerosis (ALS). The authors concluded from their results that adult onset PLS might be an inherited disease, and that there was a continuum between PLS and ALS, as both diseases coexisted in the reported kinships [1].…”
Section: Familial Clustering Of Primary Lateral Sclerosis and Amyotro...mentioning
confidence: 97%